Quality Analysis of Instant Pu-erh Tea Produced by Liquid-State Fermentation with Pantoea camelliae Z09 - XIE Yanxia, ZHU Yuanmin, YANG Zixi, XU Pan, SHI Chuan, YU Longjiang (Shipin Kexue)
This study aimed to evaluate the quality attributes and components of instant Pu-erh tea produced by liquid-state fermentation with Pantoea camelliae Z09. Colorimetric analysis and headspace-solid phase microextraction (HS-SPME) coupled with gas chromatography-mass spectrometry (GC-MS) were used for a comparative evaluation of instant tea samples made from non-fermented sun-dried tea leaves (UIPT), sun-dried tea leaves subjected to natural liquid-state fermentation (NIPT) and inoculated liquid-state fermentation with P. camelliae Z09 (PIPT) for 24 h. Sensory evaluation revealed that PIPT infusion had a reddish brown color, a mellow and slightly sweet taste, and a strong floral and fruity aroma, which was distinct from UIPT and NIPT infusions. A total of 29 volatile components were detected in PIPT infusion, including phenylethanol and methyl nonyl ketone, which contribute to the aroma of rose and citrus oils. In addition, the analysis of the non-volatile composition of PIPT indicated that P. camelliae Z09 promoted the degradation and conversion of theanine and catechins while significantly increasing the synthesis of theabrownins, thereby increasing the mellow taste of instant Pu-erh tea. Correlation analysis showed that theanine, catechin and epigallocatechin gallate were significantly negatively correlated with the synthesis of theabrownins (P < 0.05), indicating that they might be involved in the synthesis of theabrownins. In addition, the contents of theabrownins, theanine, catechin, soluble proteins and total soluble sugars had significant effects on the L*, a* and b* values. The results of multiple batches of scaled-up fermentation showed that instant Pu-erh tea (F-PIPT) prepared in a 100 L fermenter was superior to PIPT with respect to infusion color quality and key ingredient contents, and the scale-up production was feasible and stable. This study fills the gap in the application of bacteria in the liquid-state fermentation of tea and provides a new idea for the development of quality tea products.